Цари и боги Азиатской Скифии (по материалам кургана Аржан-2) - Чугунов, К.В. (Археологія і давня історія України, 2018)
В статье делается попытка определить статус
мужчины и женщины, похороненных в основном
захоронении кургана Аржан-2 в Туве. На основании данных археологии и работ по реконструкции
мифологии скифо-сакских племен, делается вывод о том, что мужчина был «царём» с атрибутами
первопредка, а женщина ассоциировалась с богиней царского очага. The article is devoted to the reconstruction of the
mythology of the nomads of the Tuva early Scythian
times. An attempt to determine the status of a man and
a woman buried in the burial of the Arzhan-2 mound
is made on the basis of archaeological data and works
on the reconstruction of the mythology of the Scythian-
Saka tribes. The study showed that the man was a «king» with the attributes of Yima’s progenitor, and the
woman was associated with the goddess of the royal hearthstone Tabithi. In addition, the role of gold in the
funeral rites of early nomads and the correspondence of archeology and written sources are examined.